Effects of inflammation on the transition dairy cow - Farney, Jaymelynn Kay (Kansas State University, 2012)
The transition into lactation is a period of primary concern to dairy producers because of the tremendous incidence of health disorders observed during this time. Two common disorders that lead to decreases in production and retention within the herd include fatty liver disorder (FL) and ketosis. These two disorders have been commonly associated with negative energy balance, yet recently it has been hypothesized that inflammation is a contributor to the etiology of these disorders. Three individual projects were completed for this dissertation, all involving inflammation. The role of endogenous inflammation was determined by administration of sodium salicylate (SS) to cows for 7 d after parturition, and metabolites and production responses were evaluated. Overall it appears that SS induced hypoglycemic conditions and increased triglyceride accumulation in the liver (while administered), increased lipid mobilization and ketones (2 weeks after administration ended), and increased whole lactation milk production in older cows. A sensitive, specific sandwich ELISA for bovine tumor necrosis factor-[alpha] was developed, which provided the ability to measure “normal” circulating levels of this cytokine. The final study involved inducing inflammation by daily injections of the TNF[alpha] to the early lactation dairy cow. In this model, cows receiving TNF[alpha] had a reduction in dry matter intake, water intake, and decreases in milk production and milk components. Overall, it appears that inflammation is involved in the normal biology of the transition dairy cow and disrupting this can lead to interesting negative effects and some improvements of production; however, when inflammation is much greater it can lead to negative production effects.
Effects of inflammation on transition dairy cows
Keywords: Transition dairy cow; Non steroidal anti-inflammatory drug; Tumor necrosis factor-alpha; ELISA; Animal Sciences (0475)